Shiny objects - Benedict, Dianne, 1941- (Iowa City : University of Iowa Press, 1982)
A successful professional painter and art instructor for years, Benedict was dissatisfied that she could paint petal-perfect flowers and expensive portraits of wealthy clients, but could not capture the light on the garden at dusk or the tender hands and faces of her own children. Seven years ago she walked into a poetry workshop and found "the window I needed for my imagination." She never painted another painting, and has never stopped writing. She got her BA in English and her MFA in writing at Goddard College
Crows -- The blind horse -- Shiny objects -- Where the water is wide -- Looking for rain -- The bath -- The stone angel -- Unknown feathers.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
JSTOR
Keywords: Short stories; Nouvelles; short stories; FICTION -- General; Short stories; short stories; Short stories; Short stories; Nouvelles